BIOGAS PRODUCTION USING Aspergillus nidulans ISOLATED FROM SOIL TEAK FOREST KARE, MADIUN - Pujiati, Pujiati (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M), Universitas Negeri Semarang, 2020)
Energy is a difficult problem to deal with. The increase in energy demand is caused by increasing population growth. Therefore, the alternative energy needed is biogas. Biogas is a gas produced by the fermentation process of organic material by anaerobic bacteria. Organic material that can be used for the process of making biogas is bagasse. Biogas production process using bagasse will be pretreatment with cellulolytic molds, namely Aspergillus nidulans. The purpose of this study was to determine the effect of fermentation time and differences in substrate concentrations on the optimization of biogas production. The fermentation time used was 48 hours, 96 hours, 144 hours and 192 hours with mold concentration 0%, 20%, 40%, and 60%. Indicators to be measured were biogas pressure, biogas volume and C / N ratio. The results showed that the fermentation time and concentration of mold affected the biogas pressure and biogas volume. The most optimal biogas pressure was at 96 hours fermentation time with 60% mold concentration and 1,00249 atm while the most optimal biogas volume was 96 hours fermentation time with a concentration of 60% and 0.73 cm3.